2012
DOI: 10.1007/s11829-012-9229-9
|View full text |Cite
|
Sign up to set email alerts
|

Edge effects decrease ant-derived benefits to seedlings in a neotropical savanna

Abstract: Edge effects may lead to changes in mutualistic plant-animal interactions, such as seed dispersal, that are critical to plant regeneration. However, research into edge effects is neglected in the Brazilian cerrado, the largest neotropical savanna. We evaluated the consequences of edge effects in the cerrado for the regeneration of Erythroxylum pelleterianum (Erythroxylaceae), a shrub that benefits from seed dispersal by ants. We compared air temperature, relative humidity, and vapor pressure deficit, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
49
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 44 publications
4
49
2
Order By: Relevance
“…Indeed, our experiment with synthetic fleshy fruits showed that the decreased occurrence of a particularly beneficial ant group (i.e., large ponerines) in the disturbed forest fragments corresponded with a decline in the ants' potential dispersal benefit to plants (i.e., less frequent dispersal and shorter displacement distance of ‘fruits’). The present study indicates that the deforestation process of the Atlantic rainforest (i.e., fragmentation and other human-induced disturbances) negatively affects the potentially mutualistic interaction between ground-dwelling ants and small to medium-sized fleshy fruits, corroborating other studies on ant-fruit interactions in human-disturbed habitats [20], [31], [33], [34]. The potential decrease in the benefits resulting from opportunistic ant-fruit interactions adds up to the already pessimistic scenario faced by vertebrate-dispersed plants [4], [11], [69], since frugivores are among the first to disappear from human-disturbed forest fragments [9], [10].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Indeed, our experiment with synthetic fleshy fruits showed that the decreased occurrence of a particularly beneficial ant group (i.e., large ponerines) in the disturbed forest fragments corresponded with a decline in the ants' potential dispersal benefit to plants (i.e., less frequent dispersal and shorter displacement distance of ‘fruits’). The present study indicates that the deforestation process of the Atlantic rainforest (i.e., fragmentation and other human-induced disturbances) negatively affects the potentially mutualistic interaction between ground-dwelling ants and small to medium-sized fleshy fruits, corroborating other studies on ant-fruit interactions in human-disturbed habitats [20], [31], [33], [34]. The potential decrease in the benefits resulting from opportunistic ant-fruit interactions adds up to the already pessimistic scenario faced by vertebrate-dispersed plants [4], [11], [69], since frugivores are among the first to disappear from human-disturbed forest fragments [9], [10].…”
Section: Discussionsupporting
confidence: 91%
“…[20], [61], [65]). Pheidole species are commonly reported at fallen fleshy diaspores in tropical ecosystems (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Cagnolo et al 2006Cagnolo et al , 2009Krauss et al 2010;Marini et al 2012) and reduced plant population size (Piotti 2009;Leimu et al 2010;Vranckx et al 2012) as fragment area decreases. Also, altered abiotic conditions at the edges, including higher temperature, greater light incidence and lower relative humidity (Chen et al 1993;DaviesColley et al 2000;Christianini and Oliveira 2013), could affect plant seed germination (Ashworth and Martí 2011) and tree mortality (Murcia 1995;Laurance et al 2000). Plant species with reduced populations may sustain lower herbivory levels according to the resource concentration hypothesis (Root 1973;Connor and McCoy 2001).…”
Section: Introductionmentioning
confidence: 99%
“…plantations, as well as firebreaks and pasturelands, and is not subjected to fire since ca. 30 years (see Christianini & Oliveira 2013).…”
Section: Methodsmentioning
confidence: 99%